Hybrid control slope assisted wheelchair for the person with lower limb disabilities for hilly region. (23rd December 2022) - Chatterjee, Sudipta; Roy, Sahadev
This paper presents a hybrid control wheelchair with a slope assistive control, especially for the inclined plane and hilly region. This device uses multiple sensor networks to locate the surrounding environment and terrain to facilitate control movement. A BLDC hub motor is used to provide forward and backward motions. A high torque servo motor is used as the steering wheel. The central control unit can also be controlled by manually, automatically, and through the internet. The proposed wheelchair overcomes the limitations and drawbacks of uphill and downhill movements in the existing systems. The test was carried out using the prototype with an inclined 10-degree ramp, which proved that the slope assistance has a beneficial and significant impact in comparison with a manual wheelchair. It has been demonstrated that users can perform all required functions with a better control strategy, enhancing the effectiveness of traditional wheelchairs.